Food glorious food : from cakes to curries to Cornish pasties - favourite dishes from the search for Britain's best recipe - Burgess, Patricia, editor (London : Mitchell Beazley, 2013)
Every recipe tells a story. And every family has one - a recipe that tugs at your heartstrings, makes you laugh, brings back memories and sums up all that's great about food: its ability to delight our senses, bring people together and spread joy and happiness. Food, Glorious Food! - the book of the major new ITV1 series presented by Carol Vorderman - will be crammed full of these heart-warming and delicious recipes. Packed full of dishes from ordinary members of the public, the book will feature the food that we all love to cook and want to know how to cook. Those dishes will form the spine of the Food, Glorious Food! book. But each recipe will be so much more than just a list of ingredients and a set of cooking instructions: that's because each will be accompanied by the inspiring story of its creation, along with fascinating and revealing photos plucked from the personal archives of the recipe's creator and their family. The featured dishes will encompass old favourites like Lancashire Hot Pot, Cornish Pasties and Bakewell Tart, alongside new and inventive fusions of flavours that simply have to be tasted. Some dishes will incorporate quirky twists - for example, an extra ingredient that was originally added by mistake - while other recipes will stick to time-honoured techniques, handed down through multiple generations of the same family. In between the featured recipes will be thoughtful reflections on Britain's food heritage and the nation's love affair with home cooking. This is the definitive guide to the UK's best recipes, written for the people of Great Britain, by the people of Great Britain.